Pengaruh Kepemilikan Institusional, Kebijakan Dividen Dan Inflasi Terhadap Harga Saham Perusahaan Manufaktur Sub Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode (2019-2022) - Okawati, I Gusti Ayu Intan Okawati Intan; Kusumawati, Ni Putu Ayu (Hita Akuntansi dan Keuangan, 2024)
The results of this study indicate that institutional ownership and inflation have no effect on stock prices. Dividend Policy has a positive effect on Stock Prices. It is suggested that manufacturing companies in the Consumer Goods Industry sub-sector listed on the Indonesia Stock Exchange should continue to increase shareholder confidence in the company, so companies must be able to show good company performance, especially in generating profits, so as to attract investors to invest in a company. company. And items for disclosure of corporate social responsibility should be in accordance with Law no. 40 of 2007 concerning limited liability companies so that they are in accordance with the conditions that exist in society.